Sustainable Ecosystem-Based Capture Fisheries Management in Arut River: Socio-Economic Perspective - Hasaruddin Hasaruddin; Rohmelawati Rohmelawati (Relasi : Jurnal Ekonomi, 2026)
This study analyzes the socio-economic conditions of fishermen and identifies the factors contributing to the decline in fish catches in the Arut River, West Kotawaringin Regency, Indonesia. A descriptive qualitative approach supported by quantitative data was employed. Data were collected through interviews with 10 traditional fishermen, field observations, documentation, and secondary data from relevant government reports and literature. The findings indicate a significant decline in fish catches over the last 3–5 years, from 5–10 kg/day to 2–4 kg/day. During the dry season, catches decreased by 44%–57% compared to normal conditions. This decline is caused by environmental factors, including reduced river discharge, increasing water temperature, and declining water quality, as well as anthropogenic factors such as pollution, overfishing, and illegal fishing practices. These conditions have also resulted in unstable incomes and increased socio-economic vulnerability among fishermen. The study concludes that fisheries management in the Arut River remains ineffective due to weak institutional coordination and limited enforcement. Therefore, the implementation of an Ecosystem Approach to Fisheries Management (EAFM) through co-management between government and local communities is recommended to ensure sustainable fisheries resources and improve fishermen welfare.